Spreminjanje gozdnatosti kraškega gozdnogospodarskega območja v obdobju 1830-2000 - Šebenik, Domen (Gozdarski vestnik, 2004)
The authors present the changes in the forest cover of the Karst forest management region on the basis of an analysis of the chorological map of the Littoral dating from 1830 and on the basis of data on the forest cover collected up to the year 2000. In 1830 the forest covered 19.3 % of the totalarea, the least forest areas were in the Karst region (14.5 %), somewhat more in Istria (20.8 %), while the most forested area was that of the sub-mediterranian pre-Dinaric region (23.2 %). The forest was very much fragmented as patches smaller than 1 hectare accounted for 50 % of the total forest area and only 5 % of the forest area were patches larger than 50 ha. The area covered by forest increased due to afforestation and to the overgrowing of abandoned agricultural land, so that in the year 2000 the forest accounted for as much as 55 % of the total surface. Forest cover increased most in the Karst region and least in Istria. Trends show that forest areas in the Karst forest management region will continue to increase.
Keywords: gozdovi; Kras; zaraščanje